Framed Communities: Translating the State of the Nation - Janse van Rensburg, Thelmé; Feinauer, Ilse (Stellenbosch Papers in Linguistics Plus, 2014)
The South African President delivers a State of the Nation Address every year. In this speech he conveys his opinion on the current state of affairs in the country. Since it is impossible for the President to accommodate all 11 official languages of the country, most of his speech is given in English. A few weeks after the Address, the speech is translated into all 11 languages and can be viewed on the Government’s official website. Unfortunately, by that time the Address is considered old news. The country’s different media channels report extensively on this speech. These reports can, however, be regarded as much more than simple commentaries on the speech – they are in fact reframed and rewritten versions of the speech that affect, shape and sustain the opinions and ideologies of their readers. These media channels also provide the vehicles through which common links can be established between supporters of the same media to reinforce their belief that they form part of an established community (Bielsa and Bassnett 2009:33). In situations where communication is present or necessary, it is impossible to escape the process or effect of framing, as framing implies “‘how speakers mean what they say’” (Tannen and Wallat 1993:60, in Baker 2006:105). Therefore, the presence and effects of framing should never be ignored. In the case at hand, it is through rewriting the President’s speech to fit the framework of the particular media channel that framing takes place. Baker (2006:3) supports the integral role framing plays in (intra- or interlingual) translation by introducing the idea that the translated and reformulated narratives that we are exposed to on a daily basis constitute the everyday stories that shape the way we perceive reality. Therefore, it is vital to investigate this process and how it affects both the target text and the target readership. In this exploration of rewritings of the State of the Nation Address, the researchers focus on three different South African publications, and how each uses the same source text to create vastly differing target texts. By catering for their target markets, these publications maintain or shape a specific point of view; by focusing on specific parts of the source text that would interest their readership, they, at the same time, only expose the readers to these sections of the speech, and subsequently frame the readers’ perception of the Address, the President, and ultimately, their country.